Aspartate racemase, generating neuronal D-aspartate, regulates adult neurogenesis - Kim, Paul M. (National Academy of Sciences, 2010)
D-Aspartic acid is abundant in the developing brain. We have identified and cloned mammalian aspartate racemase (DR), which converts L-aspartate to D-aspartate and colocalizes with D-aspartate in the brain and neuroendocrine tissues. Depletion of DR by retrovirus-mediated expression of short-hairpin RNA in newborn neurons of the adult hippocampus elicits profound defects in the dendritic development and survival of newborn neurons and survival. Because D-aspartate is a potential endogenous ligand for NMDA receptors, the loss of which elicits a phenotype resembling DR depletion, D-aspartate may function as a modulator of adult neurogenesis.